Growth and yield of lodgepole pine stands disturbed by mountain pine beetle in the Lower Foothills of Alberta - W. Richard Dempster; Sharon Meredith (The Forestry Chronicle)
Changes in the structure and dynamics of lodgepole pine stands following the 2006 outbreak of mountain pine beetle in western Alberta were investigated by monitoring attacked permanent sample plots over the following decade and projecting future stand development with locally validated growth models. Results suggest that a wide range in growth and yield of attacked stands is likely, with projected impacts varying from minor and inconsequential modifications to full stand replacement. Severely disturbed stands are unlikely to naturally regenerate to pine. The degree to which timber production is naturally restored in such stands will depend to a large extent on the amount and composition of non-pine advance growth and regeneration. Variation in attack severity and tree species composition will, in the absence of clearcutting following disturbance, result in increased diversity in stand and forest structure. Recommendations are made for scheduling salvage and restoration operations to ameliorate losses in timber supply.